Tecnologia alternativa para tratamento seletivo de efluentes domésticos - Pizzatto, Gabriele (2012)
The effluent from the kitchen sink, dishwasher, tank/washing machine, toilet bowl, shower, sink and tub when not covered are the source of many environmental problems and public health. The current management models based on conventional technologies still present technical and economic limitations. In this context, the study aimed to develop and propose a new model of management of domestic sewage and specifically the development of an alternative technology for the preliminary treatment of wastewater generated in the kitchen sink (due to its specific characteristics). The methodology included the qualitative and quantitative characterization of the generating source and domestic effluents, methods of collection, transportation and conventional treatment of domestic sewage and explanation of the advantages/disadvantages of the methods, processes and conventional technology. The results of the monitoring activities and habits of a family allowed determining the water consumption and the consequent generation of waste in each of the sources, which resulted in a correlation that will assist in the calculation of generation capacity/production of domestic sewage in homes and corresponding diagnosis. The tests performed with commercially available technologies for treating the effluent from the kitchen sink (grease trap) have identified the technical limitations of these technologies and the consequence was that the development of a new technology with innovative features called "ash for treatment of effluent from the sink kitchen with simultaneous separation of fat and settleable solids - Model UNIOESTE" innovative technology and in the process of patenting. It therefore contributes to mitigating the negative impacts that result from inadequate management of domestic wastewater using for such technological innovations resulting from intellectual activity with experimental validation. Key-words: domestic sewage, effluent from the kitchen sink, waste management, grease trap.